Tinjauan dan Pengembangan Potensi Desa Wisata Ramah Anak: Studi Kasus di Desa Blembem, Ponorogo, Jawa Timur - Muhammad 'Azam Muttaqin, M.Pd 'Azam (Lentera Salam Institute, 2024)
The development of a Child-Friendly Tourism Village in Blembem Village, Ponorogo, East Java, is a community service program aimed at enhancing the potential of local tourism. Blembem Village has a rich natural and cultural potential, yet it has not been maximized as a Child-Friendly Tourism destination. This community service program utilizes a participatory approach, involving the local community in the development process. The methods used include surveys, group discussions, and training. The results of this program demonstrate an increased awareness among the community about their tourism potential, as well as improvements in infrastructure and services for Child-Friendly Tourism. The development of the Child-Friendly Tourism Village is expected to provide economic and social benefits, serve as a stimulus for children's growth and development, and protect children, while also preserving the cultural heritage of the local community.